PENGARUH ASAM CUKA SAGUER TERHADAP SIFAT ORGANOLEPTIK DAGING ITIK SERATI (Cairina moschata) - Illy, Nilamsari; Wahyuni, Indyah; Kalele, J. A.D.; Lontaan, N. (Universitas Sam Ratulangi, 2016)
THE EFFECTS OF PALM JUICE VINEGAR TOWARDS THE ORGANOLEPTICS OF MUSCOVY DUCK MEAT (Chairina moschata). People in North Sulawesi are continued to develop duck farming. Most of them run their farm with traditional system. The species of duck developed in North Sulawesi of Chairina moschata is called Muscovy duck. Special treatments were applied in cook processing of duck meat especially to eliminate stink and tough texture. Palm juice vinegar containing acetic acid has many roles when it was added in foods stuffs including duckâ€™s meat. The aim of this research was to evaluate the organoleptic taste of duck meat immersed in palm juice vinegar. The objects of this research were breast part of duck meat immersed and in juice vinegar and stored during 4, 8 and 12 days. This research used completely randomized design involving 4 treatments with 40 untrained panelists as replication. Observed variables were colors, flavors, meat tastes and meat tenderness. Data was analyzed using ANOVA and Duncan Multiple Range Test (DMRT) for further significant treatments. The results showed that immersion treatment of duck meat in palm juice vinegar stored during 4, 8 and 12 days gave significant effects (P<0.01) to organoleptic of duck meat. Further test with DMRT showed that immersion of duck meat in 12 days palm juice vinegar can be accepted by the panelists as the best treatment. Â Keywords: Organoleptic test, duck meat, palm juice vinegar